AIE Active Carbazole‐Benzothiazole Based ESIPT Motifs: Positional Isomers Directing the Optical and Electronic Properties. Issue 5 (21st February 2017) - Padalkar, Vikas S.; Kuwada, Kenji; Sakamaki, Daisuke; Tohnai, Norimitsu; Akutagawa, Tomoyuki; Sakai, Ken‐ichi; Sakurai, Tsuneaki; Seki, Shu
Abstract: Three positional isomers based on carbazole (Cz) and hydroxy benzothiazole (HBT) were synthesized targeting solid state organic emitters by Suzuki coupling reaction and their optical, structural and electronic properties were compared. The changing of position of HBT unit on 9‐phenyl‐9 H‐ carbazole alters the optical and structural properties significantly. The synthesized compounds are highly emissive in solid and aggregated state ( Φ f =∼ 40 %) and weakly emissive in solvents of different polarities ( Φ f =2.6‐17 %). The difference in the fluorescence quantum efficiency among the positional isomers can be assigned to conformational differences which were further supported by geometrical parameters computed by DFT computations. The present Cz‐HBT based ESIPT motifs are endowed with aggregation induced emission (AIE), solid state and polarity sensitive emission with large Stokes shift. Abstract : Influence of positional isomers on solid state emission properties of carbazole based ESIPT motifs is discussed in detail. The present carbazole‐ hydroxy benzothiazole (ESIPT motifs) molecules are endowed with aggregation induced emission, solid state, and polarity sensitive emission with large Stokes shift.